(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Death in custody is a death of a person in the custody of the police or other authorities or while in prison. When the causes are studied, they are usually from natural causes with the heart diseases constituting the majority of cases. We present a case of death in custody from spontaneous liver rupture, a rare condition with very few cases reported in literature. We are not aware of any reported case of death in custody secondary to spontaneous liver rupture. High index of suspicion is required for early diagnosis of spontaneous liver rupture and should be considered as a possible cause of death in custody. Adequate medical history of the detainee is important and crucial as they can detect fatal condition and the prison staff must act promptly to address any medical concerns of the inmates.